Pengaruh Pupuk terhadap Pertanaman Kacang Hijau dan Residunya pada Tanaman Kacang Tunggak - Sri Ayu Dwi Lestari; . Sutrisno; Henny Kuntyastuti (Jurnal Ilmu Pertanian Indonesia, 2018)
The objective of this research was to determine the effect of fertilization on four varieties mungbean in ultisol acid soils and its residual on cowpea. The experiment was conducted at the screen house of Indonesian Legumes and Tuber Crops Research Institute (ILETRI), Malang, East Java, from November 2014-April 2015. Two types of research conducted sequentially, the first planting was four mungbean varieties and the second planting was cowpea (continued from the first planting) without additional fertilizer. This experiment was laid out in split plot design, replicated three times. In the first planting, mungbean as the main plot, namely Kenari (V1), Murai (V2), Kutilang (V3), and Vima 1 (V4). Fertilizer rates as the sub plot, namely control or without fertilizer (P0), 300 kg Phonska/ha (P1), 1500 kg cow manure/ha (P2), 3000 kg cow manure/ha (P3), and 5000 kg cow manure/ha (P4). The cowpea variety used in the second planting was KT 4, with the experiment design following the first planting. The results from first planting showed that growth of mungbean varieties was relatively same at ultisol acid soils, and seed yield can increase by application 300 kg/ha Phonska or 3000 kg cow manure/ha. The growth of cowpea showed the best result on both fertilizers indicating the presence of fertilizer residue from first planting.